Resistencia de concreto con agregado de alta absorción y baja relación a/c - Solís, R. G.; Moreno, E.; Arjona, E. (Revista ALCONPAT, 2012)
Concrete strength depends on the cement paste quality and on the characteristics of the aggregates. The former is controlled by the water to cement ratio, while the properties of the aggregate, in general, cannot be manipulated as it is customary to employ the ones available near the construction site. In many regions rocks with no desirable properties are employed as aggregates. Therefore, the aim of this study was to answer the question about what would that be the maximum compressive strength attainable in concrete made with a specific type of aggregate obtained from crushed limestone of high absorption. Concrete mixtures involved six water to cement ratios and two sizes of coarse aggregate. It was concluded that with this type of aggregate it is possible to made concrete with compressive strength up to 500 k/cm2 of f’c.Key words: absorption; compressive strength; concrete; limestone aggregate; water/cement ratio; resistance.